Phytochemical Elucidation and Antioxidant Activity of Seeds from Three Prickly Pear (Opuntia ficus-indica L.) Cultivars from Algeria - Abderrahmene Bouaouich , Faiza Bouguerche , Houda Mahiaoui , Gregorio Peron ,and Hamdi Bendif (My University, 2023)
In this study, the characterization of fatty acids and secondary metabolites in seeds of three cultivars of Opuntia ficus-indica L. (O. ficus-indica, yellow, orange, and green) harvested from the Souk Ahras area in Northeast Algeria was performed. The antioxidant activity of seed extracts was also assessed by using two methods, namely FRAP and DPPH tests. Results show that total phenolic content (TPC) ranged from 63.02 to 81.80 mg gallic acid equivalents (GAE)/100 g of seeds. The yellow cultivar had the highest TPC, followed by the orange and green cultivars. Concerning flavonoids and tannins, the orange cultivar showed higher concentrations, corresponding to 2.97 mg quercetin equivalent (QE)/100 g and 5.60 mg catechin equivalent (CE)/100 g, respectively. Analysis of the seed extracts by HPLC revealed the presence of phenolic compounds, including gallic acid and chlorogenic acid, while the GC analysis of oil showed that prickly pear oil is a major source of essential fatty acids (C18:2). The antioxidant activities of extracts from the three cultivars were comparable. The EC50 for the reduction of ferric iron was almost 0.05 g/mL for all extracts. Regarding the scavenging of DPPH, green and yellow cultivars showed the highest capacity (EC50 = 0.26 g/mL). Linear correlations between the content of some antioxidants (flavonoids, tannins) and different activities were observed, indicating their participation in the latter. Above all, a significant inverse correlation between the total flavonoid content and the EC50 calculated for the reducing activity of seed extracts was observed (r = −0.657; p ≤ 0.05). Overall, the results indicate that the seeds of O. ficus-indica growing in Algeria can be exploited as valuable sources of table oil, cooking oil, and antioxidants. Keywords: Opuntia ficus-indica; seeds; antioxidants; polyphenols; antiradical activity
Abderrahmene Bouaouich